Non-Compliance Practices in Emergency Public Procurement Context of Handling COVID-19 Pandemic in Indonesia - Sugimin Sugimin (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2022)
This study aims to explore emergency provisions in regulations and policies of Indonesia’s public procurement system, to examine non-compliance practices with regulations and procedures by procurement actors pertaining to COVID-19 emergency public procurement, and possible recommendations of overcoming its detrimental effects. This study uses normative juridical research by examining library materials and the main data source is secondary data including literature review, regulations, and the audit findings. The result showed that emergency public procurement speeds up the public procurement process, but it was found non-compliance practices with regulations and procedures by procurement actors in every stage of the emergency public procurement, so it creates inefficiency, increases the risk of wasteful spending of state finances and even more it may lead to financial losses. To address this, governments or LKPP can consider reviewing existing emergency public procurement regulation (LKPP Regulation 13/2018) by establishing the detailed emergency public procurement documents and procedures and regulating a list of reference prices or the maximum price limit of certain goods by a Circular Letter of the Head of LKPP to prevent and avoid wasteful spending of state finances or an indication of state financial losses.